A literatura e suas apropriações por jovens leitores - Maria Zelia Versiani Machado (2003)
This research analyses what youngsters aged between 10 and 14, and that are met in the process of human formation read and how they interact with literature books in two school contexts that, despite being linked by a project named Giroletras, characterize different possibilities of literature reading, because social, historical, economical and cultural conditions that define the literary literacy of one reader community and another are distinct. The thesis proposes a development that first considers the school practices of literary reading in the mediation spaces of libraries and classrooms, through the analysis of literature actions and representation implicit in the discourses and in the practices of the mediators. All of this is necessary in order to have its main aim, which is the youngster appropriation way, reached later. In the school library and in the classroom, the discourses woven about literary reading insinuate different ways of relation of the readersubject with the books. The first space the library is easily seen when one tries to understand the place occupied by literature in schools, because it is there that the possible mediation of literary reading is detached from the restrict scope of didactic mediation and it is where, supposedly there is less assessment. The classroom, on the other hand, gives the appropriation, the character of making strategies dynamic, as this mediation is superimposed by less or more systematic actions of book circulation and reading socialization. The way young readers appropriate literature constitutes the central stage of this work. It is there that the analyses of the possibilities given by the mediation in school reading spaces - library and classroom - join themselves. The readers talk about their preferences and what they understand about this type of reading. This data allows to categorize the amount of dependence established between the readers and the school practices, in respect to the reader formation in relation to his autonomy. This gathering projects a map of choices, that suppose contemporary rules that drive the literature field for youngsters in Brazil. Without these rules the ways of appropriation that want to be characterized can not been seen deeply .